Nursing in the face of health literacy, food and non-communicable chronic diseases in the elderly: integrative literature review (Research, Society and Development, 2022)
Objective: to identify in the scintific literature the role of nurses related to functional literacy in health of the health of the people with chronic non-communicable diseases and their relationship with adequate nutrition. Methodology: Integrative literature review conducted in February 2022.The following electronic databases were used for the selection of articles: Medical Literature Analysis and Retrievel System Online (MEDLINE) via National Library of Medicine (PubMed); Latin American and Caribbean Literature in Health Sciences (LILACS) and Nursing Database (BDENF) via Virtual Health Library (VHL); Scientific Electronic Library Online (Scielo); Web of Science; ScieVerse (Scopus). The definition of the fundamental question of this study was carried out through the Population/Patient/Problem - Interest - Context, Time (PICoT) strategy: "What scientific evidence on functional literacy in health related to adequate nutrition of the healthy people with chronic non-communicable diseases?". Results: We identified four studies that identified the low level of Functional Literacy in Health in the Elderly, with the age and schooling as primary factors. Conclusion: the planning of health actions in order to promote functional literacy in health is necessary for treatment support and success, emphasizing the role of the nursing team in this process.